2014
DOI: 10.1186/1471-2350-15-59
|View full text |Cite
|
Sign up to set email alerts
|

A large de novo9p21.3 deletion in a girl affected by astrocytoma and multiple melanoma

Abstract: BackgroundAssociation of melanoma, neural system tumors and germ line mutations at the 9p21 region in the CDKN2A, CDKN2B and CDKN2BAS genes has been reported in a small number of families worldwide and described as a discrete syndrome in melanoma families registered as a rare disease, the melanoma–astrocytoma syndrome.Case presentationWe here studied two young patients developing melanoma after radiotherapy for astrocytoma, both reporting lack of family history for melanoma or neural system tumors at genetic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…Although the contribution of ANRIL expression to neural system tumours remains unknown, SNPs which alter its expression, have been associated with numerous diseases including coronary artery disease, stroke, diabetes as well as melanoma and glioma 36. Most recently, Frigerio et al 37 reported a patient with both astrocytoma and multiple melanomas with the largest constitutive deletion described to date involving 9p21.3 and spanning approximately 2135 Mb. Our proband, reported herein, adds to this growing list of families with large deletions extending beyond CDKN2A , thus raising the question of whether or not this could represent an emerging contiguous gene deletion syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Although the contribution of ANRIL expression to neural system tumours remains unknown, SNPs which alter its expression, have been associated with numerous diseases including coronary artery disease, stroke, diabetes as well as melanoma and glioma 36. Most recently, Frigerio et al 37 reported a patient with both astrocytoma and multiple melanomas with the largest constitutive deletion described to date involving 9p21.3 and spanning approximately 2135 Mb. Our proband, reported herein, adds to this growing list of families with large deletions extending beyond CDKN2A , thus raising the question of whether or not this could represent an emerging contiguous gene deletion syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…37 Larger scale chromosome 9p21 alterations (including deletions involving the CDKN2A / CDKN2B / CDKN2BAS gene cluster up to the MLLT3 gene) have been described in some isolated cases. 38–41 Kaufman et al described this syndrome in 1993 when they reported concurrent CMMs and multiple types of nervous system tumors (NSTs) in eight members of a family over three generations. 42 Later, Azizi et al reported that 17 individuals with CMM, among 15 families, had one or more additional relatives with tumors of the nervous system.…”
Section: 3 Melanoma-astrocytoma Syndrome (Omim 155755)mentioning
confidence: 99%
“…38–40, 44 A positive association between radiotherapy for the NSTs and the incidence of CMM in these patients has been proposed, but remains unsubstantiated. 41 …”
Section: 3 Melanoma-astrocytoma Syndrome (Omim 155755)mentioning
confidence: 99%
“…Melanomas 190 were all between stages II and V, and were verified by a 191 qualified dermatopathologist. Upon review, melanoma 192 specimens with less than 60% tumor tissue (such as 193 specimens with a brisk lymphocytic infiltrate) were ex-194 cluded from study.…”
mentioning
confidence: 99%
“…CDKN2B is one of the 1047 genes located at 9p21 and has been shown to be 1048 deleted in melanoma [6,192] and other cancers such…”
mentioning
confidence: 99%